Exploring the multiple effects of nifedipine and captopril administration in spontaneously hypertensive rats through pharmacokinetic‐pharmacodynamic analyses - Akiko Kiriyama; Shunsuke Kimura; Shugo Yamashita (Wiley, 2024)
Abstract This study assessed the pharmacokinetics (PKs) and pharmacodynamics (PDs) of two antihypertensive drugs, nifedipine and captopril, by exploring their main (blood pressure [BP]) and secondary effects (heart rate [HR] and QT interval [QT]) in spontaneously hypertensive rats. This study aimed to assess the relationship between PKs and PDs. Using these PD parameters, BP, HR, and QT during coadministration were estimated. The coadministration of nifedipine and captopril resulted in an increase in nifedipine's total body clearance (CLtot) and a reduction in its mean residence time (MRT) with an increase in the terminal elimination half‐life (t1/2) and volume of distribution at steady state (Vdss) of captopril. However, no significant PK interactions were observed. During monotherapy, BP reduced rapidly following nifedipine infusion. Subsequently, despite the increase in nifedipine plasma concentration, BP recovered, likely because of homeostasis. Similar results were observed with coadministration. Subsequently, BP demonstrated a sustained reduction that was greater than or equal to the additive effect estimated from each PK. Captopril exhibited a minimal effect on HR, except for a transient increase observed immediately after starting infusion, consistent with observations during coadministration. Subsequently, the HR reduction was nearly equal to that calculated from the nifedipine PK. QT prolongation was more rapid with captopril than with nifedipine. Although QT prolongation during the initial 60 min of coadministration was approximately the sum of both effects, the recovery period to baseline QT was faster than that in the simulation.